Adult-Onset Acute Disseminated Encephalomyelitis with Epstein-Barr Virus Infection. (4th June 2022) - Murasawa, Emika; Matsuda, Masazumi; Ishiyama, Koichi; Shinozaki, Tetsugaku; Murata, Toshiki; Hashimoto, Manabu
Abstract : We present the case of a 22-year-old man who was diagnosed with tonsillitis and treated with antibiotics. Although the symptoms subsided, 1 week later, he presented with weakness in the lower limbs and was hospitalized. The weakness in the lower limbs worsened; he developed difficulty speaking and was transferred to our hospital. Laboratory tests showed a white blood cell count of 10, 600/ μ L (24% atypical lymphocytes). Positive results were obtained for immunoglobulin M (IgM) antibody against Epstein-Barr virus (EBV) viral capsid antigen. EBV-deoxyribonucleic acid quantification in blood yielded positive results. Magnetic resonance imaging (MRI) revealed a hyperintensity in the spinal cord at the Th11 level of the lower spine on T2-weighted imaging (T2WI). In addition, T2WI and fluid-attenuated inversion recovery imaging showed hyperintense lesions on the right cerebral peduncle, bilateral thalami, posterior leg of the left internal capsule, and right corona radiata. We diagnosed acute disseminated encephalomyelitis (ADEM) with EBV and initiated steroid pulse therapy. Symptoms, along with the lesions seen on MRI, subsequently ameliorated. This case suggests that ADEM can be difficult to diagnose, but careful diagnosis is crucial since appropriate treatment is necessary to improve the symptoms.